Dasar Rasionalitas Pertimbangan Hakim Dalam Penjatuhan Pidana Tambahan Pemecatan Prajurit TNI Pelaku Tindak Pidana Narkotika: Studi Kasus Putusan Nomor 73-K/PM.III-12/AD/V/2024 - Imelda Kusuma Sari; Rusmilawati Windari (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Narcotics crime in the military environment is a serious offense that not only violates general criminal law, but also violates the code of ethics and discipline of Indonesian National Army (TNI) soldiers. This study aims to analyze the basis of the judge's consideration in imposing additional punishment of dismissal against TNI soldiers who commit narcotics crimes. The research method used is normative legal research using a statutory approach and a conceptual approach where cases that have permanent legal force (inkracht van gewijsde) are studied by the author from the judge's consideration to the verdict. The results of this study indicate that the rationality of the judge's consideration in imposing additional punishment of dismissal is based on several fundamental aspects: (1) The impact of actions on military institutions (2) Factors of violation of the code of ethics and discipline of TNI soldiers (3) Consideration of professionalism and integrity of TNI soldiers.